2013
DOI: 10.1111/jocs.12176
|View full text |Cite
|
Sign up to set email alerts
|

C oncomitant Percutaneous Coronary Intervention and Transcatheter Aortic Valve Replacement: Safe and Feasible Replacement Alternative Approaches in High-Risk Patients with Severe Aortic Stenosis and Coronary Artery Disease

Abstract: In our small series of patients presented we demonstrate that PCI and TAVR performed concurrently in the hybrid operating room is a feasible option in patients undergoing TAVR with coexisting CAD. Furthermore, we propose this single-stage approach in such high-risk patients as it decreases the number of procedures performed and may theoretically lower cost and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Our results do not support the hypothesis reported by other authors that high-risk patients requiring AVR and CABG should be the target of future treatment strategies such as endovascular and/or hybrid procedures. 22,23) The recent American Heart Association (AHA)/ American College of Cardiology (ACC) guidelines state that CABG is reasonable in patients undergoing valve repair or replacement with significant CAD (≥70% reduction in luminal diameter in major coronary arteries or ≥50% reduction in luminal diameter in the left main coronary artery). (Class 2A, Level of Evidence: C).…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not support the hypothesis reported by other authors that high-risk patients requiring AVR and CABG should be the target of future treatment strategies such as endovascular and/or hybrid procedures. 22,23) The recent American Heart Association (AHA)/ American College of Cardiology (ACC) guidelines state that CABG is reasonable in patients undergoing valve repair or replacement with significant CAD (≥70% reduction in luminal diameter in major coronary arteries or ≥50% reduction in luminal diameter in the left main coronary artery). (Class 2A, Level of Evidence: C).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the standard treatment option for patients with severe AS and CAD has been surgical aortic valve replacement (AVR) with CABG. After the introduction of transcatheter aortic valve implantation (TAVI), new combined models of treatment are being developed with additional use of percutaneous coronary intervention (PCI) and/or balloon aortic valvuloplasty (BAV) if needed . The previous studies have confirmed that PCI is feasible and safe in selected high‐risk or inoperable patients with symptomatic severe AS .…”
Section: Introductionmentioning
confidence: 99%
“…For patients scheduled for TAVI, the most frequent approach to treat coexisting CAD is staged PCI typically performed a few weeks before TAVI . On the other hand, concomitant PCI and TAVI has also been shown to be feasible . Similarly, patients with significant CAD scheduled for BAV can be treated with PCI at the time of BAV (as a single procedure) or staged PCI .…”
Section: Introductionmentioning
confidence: 99%
“…The Bern Transcatheter Aortic Valve Implantation Registry demonstrated that there is an additive increase in cardiovascular mortality in patients with a SYNTAX score >22 than in those with a lower score due to myocardial infarction which might be decreased by concomitant coronary revascularization. The benefits of this hybrid approach include limiting the number of procedures, decreasing contrast dye exposure, and decreasing the risk of myocardial infarction in the post‐operative period …”
Section: Discussionmentioning
confidence: 99%